(untitled) (GnosisWisdom, 2025)
This study assessed the effect of implementing a Fintech business model based on a digital wallet on the payment system in micro and small enterprises (MSEs) in Huancayo, Peru. A pre-experimental pre-post design (O₁ → X → O₂) was employed with eight establishments selected via convenience census sampling. Evaluated indicators included security, ease of use, operating cost, and service time, measured through customer surveys, semi-structured owner interviews, and structured observation. Results showed statistically significant differences (paired-samples t-test, p < 0.05) across all indicators: security (+30.7 points), ease of use (+42.0 points), operating cost (–22.0 points), and service time (–45.1 points). It is concluded that digital wallet adoption significantly enhances operational efficiency, security, and customer experience in the payment systems of the assessed MSEs, serving as a viable option for digital transformation in regional Peruvian settings with persistent unbanked gaps.